Developing a Digital Learning Interactive 3D Exploded View Automobile Brake System - Anwar, Lutfi Nuril; Sumarli, Sumarli; Ihwanudin, M. (Fakultas Teknik Universitas Negeri Malang, 2020)
This research aimed to design and develop an Exploded View 3D Model learning media on the brake system topic, as well as knowing the feasibility of learning media 3D Exploded View model on brake system topic. This study used the research and development method. The development model used the ADDIE, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of the product trial were teachers and 11th-grade students in Public Vocational High School 11 Malang. Material experts and media experts carried out the product feasibility test phase. A media test was conducted on students. The data analysis technique used questionnaire and evaluation questions, as well as descriptive statistical analysis techniques. The results of this study were an Android-based learning media in the form of a 3D Exploded View model on brake system topic, and the results of the feasibility assessment by material experts got a percentage of 89.6 percent in the category of